2015
DOI: 10.1016/j.apmr.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Use During Inpatient Rehabilitation for Traumatic Brain Injury

Abstract: Objective To describe psychotropic medication administration patterns during inpatient rehabilitation for traumatic brain injury (TBI) and their relationship to patient pre-injury and injury characteristics. Design Prospective observational cohort. Setting multiple acute inpatient rehabilitation units or hospitals. Participants 2,130 individuals with TBI (complicated mild, moderate, or severe) admitted for inpatient rehabilitation. Interventions NA Main Outcome Measure(s) NA Results Most frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
(27 reference statements)
0
51
1
Order By: Relevance
“…More detailed information on medication prevalence and use patterns in this sample is presented elsewhere. 18 Because of the large number of therapy activities, some collapsing was necessary so that models were not over-specified. OT, PT, and ST activity collapses can be found in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More detailed information on medication prevalence and use patterns in this sample is presented elsewhere. 18 Because of the large number of therapy activities, some collapsing was necessary so that models were not over-specified. OT, PT, and ST activity collapses can be found in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates were allowed to enter and be added into each model in one of five blocks: (1) patient and injury characteristics, (2) discipline-specific total minutes/week, (3) percent of stay on medications from each of 8 pharmacological classes (defined elsewhere), 18 (4) level of effort (LOE), (5) discipline-specific activity minutes/week, and (6) centers participating in the study. We computed the amount of variation explained when we allowed various combinations of the variable blocks to enter models predicting outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In acutely ill patients, one recent single-centre study ( n  = 195 patients) reported antipsychotic use in 26.7% of patients within 7 days of TBI [26]. In a recent observational study of 10 North American inpatient rehabilitation facilities, antidepressants, anticonvulsants, stimulants, and antipsychotics were used for the management of neurobehavioral complications of TBI in 67%, 47%, 28%, and 25% of patients, respectively [27]. In addition, surveys have suggested wide variations in practice patterns in regard to the choice of agents to treat neurobehavioral problems [24, 28].…”
Section: Introductionmentioning
confidence: 99%
“…As post-traumatic agitation is a complex and poorly understood complication, occurring in a heterogeneous patient population, pharmacological interventions are inadequately studied despite the frequent use of various medications [27, 28]. Given the desired impact on the resolution of agitation while limiting potential adverse effects associated with the use of these agents in the TBI population, an analysis of the literature evaluating their efficacy and safety is imperative.…”
Section: Introductionmentioning
confidence: 99%